The roles of propensity to use and precipitating events on IS related innovation adoption behaviour by entrepreneurs / Sedigheh Moghavvemi - Moghavvemi, Sedigheh (2012)
The main aim of this study is to investigate entrepreneurs behavioural intention (i.e., intention to use) and use behaviour toward IS related innovation adoption. Among all these competing IS adoption models, Unified theory of acceptance and use of technology (UTAUT) has been considered as the most vigorous and prudent to assess the IS adoption behaviour by individuals. Although UTAUT is a robust and parsimonious theory, and many prior studies in IS adoption behaviour have validated and confirmed UTAUT in different contexts, there are still criticism to the theory, specifically to the predictive ability of behavioural intention to predict use behaviour. To address this gap between behavioural intention and use behaviour in UTAUT and to improve UTAUT, this study extensively synthesise related literature in other disciplines such as entrepreneurship. Research in the entrepreneurship context has identified precipitating events as a promising factor to overcome such limitations of UTAUT. Therefore, prominent behavioural intention model in IS discipline, that is UTAUT, and Entrepreneurial Potential Model (EPM) in entrepreneurship area are reviewed, analysed, synthesised to understand the human planned behavioural intention and use. To achieve this aim, this study decomposes and integrates the UTAUT and the EPM to capture different factors of technological, individual, and environmental of IS adoption behaviour by entrepreneurs.